Factors associated rural students eagerness in entering the higher education : a case study of selected schools in Beaufort / Ameera Nabeela Md. Yussof and Norisah Tahir - Md. Yussof, Ameera Nabeela; Tahir, Norisah (2014)
Every school students especially in rural area have ambition to further their study to the higher education whether public or private university. It is important to students have eagerness and preparing the students to enter in higher education. At the same time meet demand labour market besides create quality individual for the country. The study was conducted to study rural students’ eagerness to enter higher education: a case study in three selected schools. The objectives of this study were to investigate whether there an eagerness of the students to enter the higher education and to determine factors of access, family, performance and peers associated with students’ eagerness entering the higher education. A cluster sampling of 123 rural students were selected to answer the questionnaire and little bit with interview and teachers opinion about the students, eagerness to enter higher education. Data was analysed through descriptive statistics and inferential statistics. Most of the rural students having high eagerness to enter higher education and factors associated such access, family, performance and peers were significant correlation to the eagerness of the students in entering higher education. Overall, schools students especially leave in rural area having eagerness to enter higher education and it became duty of parties provided enough opportunity to students’ realization their eagerness to enter higher education.